A Strong Foundation: Early Literacy in North East India - NIKALJE, VARADA M. (THE PRIMARY TEACHER, 2015)
Epistemologically, the challenges of education are the same across stages; the nature of the challenges, however, would differ from stage to stage. Yet, the common perception remains fixated on Classes X and XII, and grudgingly on Class V. Paradoxically, Classes I and II, which are educationally extremely important since they introduce literacy to children, do not receive proportionate attention and funds. The consequences of this mind-set are particularly dismal for schools in rural and interior areas. In the light of these and related aspects, the document Padhe Bharat Badhe Bharat launched by the Government of India on August 26, 2014, is of enormous significance, as it officially gives belated academic recognition to learning in Classes I and II. This paper examines the document in the context of North East India and attempts to explore ways to leverage existing opportunities as well as make recommendations for new ones to support early reading and writing with comprehension for children in classes I and II.